Citogenômica de DNAs satélites em macacos de cheiro (Saimiri, Cebidae, Platyrrhini) - Mirela Pelizaro Valeri (2017)
Squirrel monkeys of the genus Saimiri (Cebidae; Platyrrhini) are distributed in the Amazon basin and part of Central America. The number of species and their phylogenetic relationships are controversial. Cytogenetics was fundamental in the identification of Saimiri species: all analyzed individuals until now presented a diploid number 2n = 44 with fundamental numbers ranging from 74 to 78, according to their geographical distribution. In this work, we characterized the two most abundant satellite DNAs of Saimiri boliviensis, Alpha and CapA, using RepeatExplorer and mapped them in the chromosomes of S. boliviensis, S. vanzolinii, S. sciureus and S. ustus. The alpha satellite has ~340 bp, comprises ~1% of the S. boliviensis genome and had a centromeric location in the four species. CapA comprises about 2.2% of the S. boliviensis genome and has ~1,500 bp. Its distribution on the chromosomes is related to the constitutive heterochromatin, which is mainly located in the subtelomeric regions of submetacentric chromosomes, as well as in some interstitial regions. CapA has different locations among Saimiri species, suggesting that it could be used as a taxonomic marker. We investigated the CapA presence in other primates, since it was previously described in Sapajus apella, and confirmed its presence in some genera of the three Platyrrhini families. A detailed search revealed the CapA sequence is present as a single copy located within an intron of the nitric oxid synthase 1 adaptor protein (NOS1AP) gene in humans and in the genomes of most eutherian mammals. The CapA satellite DNA of Platyrrhini has probably originated from this intronic sequence and the possible mechanisms responsible for its amplification are discussed. To our knowlodge, this is the fisrt report of a single copy intronic sequence giving origin to a satDNA. Information about the alpha and CapA satellite DNAs may contribute to the understanding of chromosome evolution in Saimiri and Platyrrhini.